Ibudilast, a Phosphodiesterase Inhibitor, in Combination with Low-dose Aspirin Potently Inhibits Guinea Pig Carotid Artery Thrombosis without Extending Bleeding Time and Causing Gastric Mucosal Injury - Matsuzawa, S.; Hoshina, K.; Sueyoshi, S.; Miyata, Y.; Manita, S.; Ooie, T.; Yasue, T.; Sasahara, T. (Arzneimittelforschung, 2012)
A combination of low-dose aspirin (ASA) and a phosphodiesterase inhibitor has been clinically tried for the secondary prevention of atherothrombotic diseases. The in vivo antithrombotic property of ibudilast (CAS 50847-11-5), a phosphodiesterase 4 (PDE4) inhibitor, was evaluated in a photochemically-induced guinea pig carotid artery thrombosis model in combination with low-dose ASA. The time required to decrease the carotid artery blood flow to the reading “zero” was defined as the time to occlusion (TTO) of the artery through thrombogenesis. Each independent use of ASA (300 mg/kg, p.o.) and ibudilast (3 and 10 mg/kg, p.o.) significantly prolonged the TTO, and ASA (300 mg/kg) significantly increased bleeding time (BT) and gastric mucosal injury. A selective PDE4 inhibitor rolipram (1 and 5 mg/kg, p.o.) tended to prolong the TTO without extending BT. ASA (100 mg/kg) plus ibudilast (3 mg/kg) and ASA (100 mg/kg) plus rolipram (5 mg/kg) markedly prolonged the TTO compared with each agent alone. Interestingly, ASA (100 mg/kg) plus ibudilast (3 mg/kg) caused a longer TTO than ASA (300 mg/kg) alone, without significant extension of BT and gastric mucosal injury as observed in ASA (300 mg/kg). These results indicate that the combination of low-dose ASA and ibudilast has a more potent antithrombotic effect than ASA alone without increasing bleeding tendency and gastric mucosal injury. The potent in vivo antithrombotic effect of this combination may be brought about by an action that is associated with PDE4 inhibition of ibudilast.
Keywords: ibudilast; CAS 50847-11-5; antithrombotic effect; phosphodiesterase 4 inhibitor; aspirin